(untitled) (Revista de História da UEG (REVHIST), 2019)
Abstract: In the eighteenth century, different social groups made up Brazilian colonial society. One of the elements that governed their organization was the division of these people into different qualities. The purpose of this article is to analyze how the idea of ​​different qualities of individuals in the colonial period and the black brotherhoods in the Pernambuco Captaincy. Thus, to analyze what was the relationship between the notion of quality and the organization of these brotherhoods of black people from the terms of commitment of the brotherhoods of the 18th century Rosary and the Book of Seating of the Brotherhood of the Rosary of Black People in Recife. Keywords: Brotherhoods of Black Men. Captaincy of Pernambuco. Terms of Commitment.